Hubungan Antara Kadar Air Tanah Dan Produksi Pertanian Di Lahan Kering - Gulo, Berkat Jaya; Hia, Apriani (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze the relationship between soil water content and agricultural production in dry land. The study was conducted in [specify location] during the planting season of [specify year] involving [specify number of] farmers who planted various types of crops, including corn, rice and soybeans. Soil water content data is measured using a tensiometer, while crop yields are recorded at the end of the season. The analysis results show that there is a significant positive relationship between soil water content and crop yields (r = [specify correlation coefficient], p < 0.01). Corn plants show the highest yields compared to other crops. This research underscores the importance of efficient water management to increase agricultural productivity in drylands and recommends the use of modern irrigation techniques and drought-resistant crop varieties as effective management strategies.